2015
DOI: 10.5194/gid-5-161-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermal-Plume fibre Optic Tracking (T-POT) test for flow velocity measurement in groundwater boreholes

Abstract: International audienceWe develop an approach for measuring in-well fluid velocities using point electrical heating combined with spatially and temporally continuous temperature monitoring using Distributed Temperature Sensing (DTS). The method uses a point heater to warm a discrete volume of water. The rate of advection of this plume, once the heating is stopped, equates to the average flow velocity in the well. We conducted Thermal-Plume fibre Optic Tracking (T-POT) tests in a borehole in a fractured rock aqu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Moreover, identification of active fractures under ambient flow conditions is much improved when the water column in the borehole is subjected to a rapid heating episode. DTS can also monitor heat movement and rate of heat dissipation due to vertical flow inside an open borehole, which can be used for locating transmissive fractures and for determining water flow rates in the borehole (Banks et al, ; Freifeld et al, ; Hurtig et al, ; Leaf et al, ; Read et al, , ; Sakaguchi & Matsushima, ; Sellwood et al, , ; Yamano & Goto, ). However, Pehme et al () clearly showed that open‐hole temperature profiles can mask many active fractures and it is well‐known that hydraulic cross connection can alter the natural flow conditions of an aquifer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, identification of active fractures under ambient flow conditions is much improved when the water column in the borehole is subjected to a rapid heating episode. DTS can also monitor heat movement and rate of heat dissipation due to vertical flow inside an open borehole, which can be used for locating transmissive fractures and for determining water flow rates in the borehole (Banks et al, ; Freifeld et al, ; Hurtig et al, ; Leaf et al, ; Read et al, , ; Sakaguchi & Matsushima, ; Sellwood et al, , ; Yamano & Goto, ). However, Pehme et al () clearly showed that open‐hole temperature profiles can mask many active fractures and it is well‐known that hydraulic cross connection can alter the natural flow conditions of an aquifer.…”
Section: Introductionmentioning
confidence: 99%